PEMBUATAN KUE KERING SAGU KEJU DENGAN MENGGUNAKAN SUBSTITUSI TEPUNG KULIT SINGKONG - Pramudito Pramudito; Faiza Rachim (Pusat Penelitian & Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2023)
Pastries are cakes that have a crunchy and very soft texture. Making pastries made from cassava peel flour can be a food effort in Indonesia to be able to reuse existing cassava waste. This type of research is experimental research. The research design used was a completely randomized design with one sample of 100% control product of farmed sago flour. (K100) and three treatments, namely 30% (P30), 60% (P60), and 90% (P90)cassava peel flour . Data processing used one -way ANOVA test with SPSS 25 program to determine the significance of the differences from the test ed products. The results of the ANOVA test in terms of taste resulted in a significant number of 0.140> 0.05. This shows that there is no significant difference in terms of taste in cassava peel cakes 100% sago tani flour with cassava peel flour substitute pastries. Then in terms of aroma it produces a significant number of 0.000 < 0.05, and in terms of texture it produces a significant number of 0.000 < 0.05. This shows that there is a significant difference in terms of aroma and texture on 100% sago tani flour pastries with substituted cassava peel flour cookies.